Interação entre ambiente e espécies no interior e na borda de um fragmento de floresta estacional semidecidual - Salim Neto, Salim Calil (2011)
This study aimed to analyze the distribution of 40 tree species with the highest absolute density within an environmental gradient edge-inside a semideciduous forest fragment. The fragment studied has 119 ha and is situated in the Pacotuba National Forest, located in the municipality of Itapemirim-ES, southeastern Brazil. The environmental variables used were: Al saturation, base saturation, soil moisture, leaf area index (LAI) and average slope. Data were collected in 39 permanent plots, and 27 (10x30m) along the edge of the fragment and 12 plots (40x50m) inside the fragment. These plots are the same used in the evaluation of phytosociology of this fragment, whose absolute density data were used in this study. The characterization of soil fertility was held at a depth of 0-20 cm, where the sample was removed for analysis and acquisition of base saturation and Al saturation. Soil moisture was obtained by the gravimetric method, and the soil was collected in the dry season(Setembro/10). The Leaf Area Index was measured by non-destructive method, using two LAI-2050 sensors, connected to dataloggers LAI-2000, LI-COR brand. As this is semideciduous forest, the IAF was obtained in two different periods, one in the dry season (September/2010) and another in the rainy season (March/2011). The average slope was determined by inclinometer. To evaluate the difference between the inside and edge of the fragment, the results of the environmental variables were analyzed by Students t test for the significance level of 5%. To analyze the species-environment interaction on the edge and inside the fragment was applied canonical correspondence analysis (CCA) using CANOCO program, and used the permutation test Monte Carlo to assess the significance of the results. For the variables related to soil, it was found by Students t test, there is no statistically significant difference between the inner and edge of the fragment at the 5% probability, while for the IAF and the average slope at the same level of probability, difference was statistically significant, indicating that the fragment has studied a greater heterogeneity between edge and interior in relation to relief and the availability of solar radiation. The first two ordination axes obtained by the CCA for 40 species of higher mass density explained 64.5% of the variance and significance was observed by Monte Carlo test (P <0.01). The first axis, explaining 36.4% of the variance observed, most correlated with soil variables, while the 2nd ordination axis correlated most significantly with LAI and average slope. However, this study found that of 40 species of higher mass density, eleven were found in greater proportion on the edge, the other eleven in the interior of the fragment and 18 species were observed in a proportionally similar in both environments. Thus, to get a better understanding of the species-environment interaction on the edge and inside the fragment, were applied two more canonical correspondence analysis. The first considering the 22 species that were observed preferentially in one of the environments, and the second involving the CCA 18 species considered in this study as generalists. According to the results, it was found that the 18 generalist species were higher under the influence of base saturation and Al saturation, while the group of species showing a preference for the environment had a strong correlation with LAI and soil moisture indicating, that for these species, the restricted or availability of solar radiation in the environment provides suitable conditions for the proper establishment of the species